Coal Mine Safety in China and Degasification of Longwall Panel Using In-Seam Directional Drilling Technology - John Feddock (International Conference on Ground Control in Mining, 2007)
A recent increase in energy demand has resulted in the rapid growth of coal consumption in the People?s Republic of China (PRC), which is the largest coal producer and consumer in the world. Reportedly, the safety issues in Chinese coal mines have been improving, but the number of fatalities and serious injuries continues to be alarmingly high. The number of fatalities from catastrophic accidents have prompted researchers to review the Chinese mine safety situation and to look for potential solutions. Marshall Miller & Associates, Inc. (MM&A), along with various collaborators, has investigated these issues as part of its work on various projects in the PRC and has discussed the concerns with relevant Chinese officials. Preliminary investigations by MM&A of coal mine accidents during 2001?2006 in the PRC indicate that 65%-78% of the total fatalities were the result of gas explosions and roof falls in underground mines. Even though the drainage of methane has been practiced for decades, current practices do not always produce satisfactory results due to technical constraints and equipment limitations. Based on prior experience of in-seam degasification at the Daning Coal Mine located in Shanxi province, MM&A believes that in-seam directional drilling technology can be a viable solution to degas the low-permeability Chinese coal deposits. This paper 1) reviews current Chinese coal mine safety conditions, 2) analyzes the advantages/disadvantages of current degasification practices in China, and 3) presents the pre-mining degasification practices for the longwall panel at the Daning Coal Mine.